The use of fermented soybean meal and squid by-product blend as a substitute for fish meal in practical diets for climbing perch, Anabas testudienus (Bloch, 1792), pond culture: Growth performance and economics analysis - Kader, Md. Abdul; Bulbul, Mahbuba; Hossain, Mohammad Mosarof; Hossain, Md. Sakhawat; Ahmed, Gias Uddin; Mian, Sohel; Hossain, Md. Arshad; Ali, Md. Eaqub (Taylor & Francis, 2019)
A feeding trial was conducted to evaluate the effects of different ratios of fish meal (FM) to a fermented blend (FB: fermented soybean meal and squid by-product blend) on growth and economic performance of climbing perch, Anabas testudineus (Bloch, 1792), in earthen ponds. Five diets were prepared where FB was substituted for 0 (D1), 25 (D2), 50 (D3), 75 (D4), or 100% FM protein (D5), while a commercial diet (D6) was used for comparison. Triplicate groups of fish (1.03 ± 0.07 g) were fed twice daily up to satiation for 70 days in earthen ponds. No significant (P > 0.05) differences were found in growth performance of fish fed D1, D2, D3, and D6 diets, while fish growth decreased significantly (P < 0.05) in D4 and D5 groups. Feed intake decreased (P < 0.05) with the increasing levels of FB with no significant difference in the feed conversion ratio, which ranged from 1.98 to 2.08. The fish survival decreased significantly in D5 alone. While considering the overall production, the total yield and economic return were found to be highest in D2 (64176.7 TK ha−1) and lowest in D5 (14418.3 Tk. ha−1). Based on the present experimental condition, it is concluded that FB can economically be included in aquafeed as a substitute for up to 50% of FM protein from the diets of climbing perch. © 2018, © 2018 Taylor & Francis.